Corrosion behavior and incorporation mechanism of Y2O3-TiO2 composite coatings fabricated on TC4 titanium alloy by plasma electrolytic oxidation - Li, Hui; Wang, Ziyao (Chemical physics letters, 2024)
A preparation method for a titanium based implant coating with good corrosion resistance. [Display omitted] •Y2O3-TiO2 coatings were prepared on TC4 by PEO reaction.•Y2O3-TiO2 coatings have compact and uniform morphology.•Y2O3-TiO2 coatings have good hydrophobicity and high corrosion resistance.•The incorporation mechanism of Y2O3 was discussed based on thermodynamics theory. The anti-corrosion of titanium alloys is a topic of concern in many fields. In our work, the Y2O3-TiO2 composite coatings were fabricated on the TC4 titanium alloy by plasma electrolytic oxidation (PEO). The reaction was conducted in an electrolyte system made up of Na2SiO3, KOH, and (NaPO3)6. The effects of additive Y(NO3)3 in the electrolyte on the microstructure, chemical component, phase structure, thickness, hydrophobicity, and corrosion resistance of the composite coatings were studied. The results show that the composite coatings prepared by PEO reaction exhibit preferable corrosion resistance. The addition of Y(NO3)3 is beneficial for thickening the coatings, reducing their porosity and pore size, and further improving their hydrophobicity and corrosion resistance. Furthermore, the incorporation mechanism of Y2O3 was discussed based on thermodynamics theory.